2016
DOI: 10.1016/j.bjorl.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the time of intranasal splinting on bacterial colonization, postoperative complications, and patient discomfort after septoplasty operations

Abstract: Silicone splints were well tolerated by the patients and any negative effects on postoperative patient comfort were limited. In fact, prolonged splint usage intervals reduced late complications. Long-term silicone nasal splint usage is a reliable, effective, and comfortable method in patients with excessive mucosal damage and in whom long-term stabilization of the bony and cartilaginous septum is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The authors concluded that silicone splints might be retained intranasally up to 10 days without increasing infection-related early complication rates. 7 Ozdogan et al examined post-septoplasty complications in 109 patients who had not received prophylactic antibiotic therapy. The authors reported 1 case (0.9%) of local infection in a patient who had the splints removed on day 3 after septoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that silicone splints might be retained intranasally up to 10 days without increasing infection-related early complication rates. 7 Ozdogan et al examined post-septoplasty complications in 109 patients who had not received prophylactic antibiotic therapy. The authors reported 1 case (0.9%) of local infection in a patient who had the splints removed on day 3 after septoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Other methods of stabilizing the septum include splints [9] clips, [10] there are recommendations of various materials including cotton tape, gauze, paraffin gauze, Telfa, Merocel, sponges, and silicone nasal splints for this purpose. [11] In septoplasties, the mucoperichondrial and mucoperiosteal flap layer on both sides of the midline cartilaginous septum are elevated, and the deviated portion of the cartilage or bone is removed. Then, the flaps are placed back together in the midline.…”
Section: Discussionmentioning
confidence: 99%
“…Medicated packs like Ribbon gauze, fingerstall packs, polyvinyl acetate sponge (Merocel), cellulose sponges, and carboxymethylcellulose, balloon tamponade has been described by Rowan V, et al [8]. Other methods of stabilizing the septum include, Splints [9] Clips [10], various materials including cotton tape, gauze, paraffin gauze, Tefla, Merocel, sponges, and silicone nasal splints have been recommended for this purpose [11]. I septoplasties, the mucoperichondrial and mucoperiosteal flap layer on both sides of the midline cartilaginous septum is elevated, and the deviated portion of the cartilage or bone is removed.…”
Section: Discussionmentioning
confidence: 99%